Powder particle, powder coating composition containing powder particle and fluororesin, and method for producing them
Patent Information
- Application Number
- JP2023141274
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-03-13
Smart Images

Figure 2025034716000001
Abstract
Description
[Technical field]
[0001] The present invention relates to powder particles that improve adhesion between a substrate and a fluororesin layer, and a powder coating composition that contains the powder particles and a fluororesin and is useful as a primer. The present invention also relates to a method for producing the powder particles and the powder coating composition. [Background technology]
[0002] Fluororesin has excellent properties such as chemical resistance, non-adhesiveness, heat resistance, and electrical insulation, and has been widely used as a coating material. Since fluororesin has non-adhesiveness, it is prone to poor adhesion when directly applied to a substrate (especially various metal substrates). Therefore, in many cases, a primer layer that has good adhesion to the substrate is provided as an undercoat layer for the fluororesin.
[0003] The present applicant has proposed polymer particles that have excellent adhesion between substrates and layers and prevent peeling due to heat, moisture, etc., and a coating composition containing the polymer particles (Patent Document 1). Although this coating composition exhibits excellent effects, it has problems such as concerns about the burden on the environment because an organic solvent is used to prepare the polymer particles, and because the resulting coating composition is an aqueous dispersion, it is necessary to add a surfactant to ensure the dispersibility of the fluororesin.
[0004] On the other hand, powder coatings are known to have the advantages of being environmentally friendly since they do not use solvents, being resource-saving since the powder is easily reused, and having excellent coating workability. Patent Document 2 discloses a powder primer composition containing a melt-soluble fluororesin powder and a polyethersulfone powder. However, there is still a demand for a coating composition having better adhesion and corrosion resistance. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2013-231098 A [Patent Document 2] JP 2022-137848 A [Patent Document 3] JP 2007-320267 A Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention aims to provide powder particles having excellent adhesion between a substrate and a fluororesin layer, and to provide a powder coating composition containing the powder particles, which has excellent adhesion and can suppress the intrusion of heat, moisture, corrosive substances, etc., thereby preventing peeling of the fluororesin laminate and improving corrosion resistance, steam resistance, and durability. Another object of the present invention is to provide a method for producing the powder particles and the powder coating composition. [Means for solving the problem]
[0007] One embodiment of the present invention is a powder particle obtained by mixing a heat-fusible polymer and a filler in water in advance to form an aqueous dispersion, and then heating the mixture. The powder particle is preferably a mixture of the heat-fusible polymer and the filler. The heat-fusible polymer is preferably at least one selected from polyimide, polyamideimide, polyamide, polyester, polyethylene terephthalate, polyphenylene sulfide, polysulfone, polyetherimide, polyethersulfone, polyetheretherketone, and polyetherketoneketone, and more preferably at least one selected from polyphenylene sulfide, polyetherimide, polyetheretherketone, and polyetherketoneketone. The filler is preferably at least one inorganic particle selected from silicon carbide, silicon oxide, aluminum oxide, zinc oxide, tin oxide, titanium oxide, barium sulfate, and carbon black. The powder particle preferably contains 30 to 300 parts by weight of the filler relative to 100 parts by weight of the heat-fusible polymer. The particle size is preferably 150 μm or less.
[0008] Also, one embodiment of the present invention is a powder coating composition containing powder particles obtained by premixing a thermofusible polymer and a filler in water to form an aqueous dispersion and then heating the mixture, and a fluororesin powder. The fluororesin powder is preferably made of a thermofusible fluororesin, and more preferably a perfluororesin. Also, the present invention is a powder coating composition containing 80-50% by weight of powder particles and 20-50% by weight of fluororesin powder based on the total weight of the powder coating composition.
[0009] Further, one embodiment of the present invention includes a process for producing a dispersion comprising the steps of: (1) mixing a heat-fusible polymer and a filler in water to obtain an aqueous dispersion; (2) heating the aqueous dispersion to remove water and obtain a solid; (3) pulverizing the solid to obtain powder particles; It is preferable that the method for producing powder particles further comprises, following the step (2), a step of heating at a temperature equal to or higher than the glass transition point of the heat-fusible polymer.
[0010] Further, one embodiment of the present invention includes a process for producing a dispersion comprising the steps of: (1) mixing a heat-fusible polymer and a filler in water to obtain an aqueous dispersion; (2) heating the aqueous dispersion to remove water and obtain a solid; (3) pulverizing the solid to obtain powder particles; (4) adding and mixing a fluororesin powder with the powder particles to obtain a powder coating composition; The present invention relates to a method for producing a powder coating composition. Effect of the Invention
[0011] The powder coating composition of the present invention has excellent adhesion between the substrate and the fluororesin layer, and can prevent the intrusion of heat, moisture, corrosive substances, etc., thereby preventing the peeling of the fluororesin laminate, and can obtain a coating film with improved corrosion resistance, steam resistance, and durability. Therefore, it can be widely used in office automation applications, chemical corrosion prevention applications, food heat processing equipment applications, sliding materials applications, automobile applications, building materials applications, and semiconductor manufacturing equipment components, etc.
[0012] In addition, the powder coating composition of the present invention does not require the addition of a surfactant, and furthermore, since no organic solvent is used in the manufacturing process, it also has the advantage of being less burdensome to the environment. Furthermore, since the powder coating composition of the present invention does not require the addition of a surfactant in the coating film manufacturing process, it is possible to improve the purity of the coating film and obtain better performance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] 1. Powder particles The powder particles of the present invention are powder particles in which (A) a heat-fusible polymer and (B) a filler are fused together. The powder particles can be obtained by premixing the heat-fusible polymer and the filler in water to form an aqueous dispersion, and then heating the mixture.
[0014] A. Heat-melting polymer The heat-meltable polymer of the present invention refers to a polymer that melts by heating, and is a polymer that has a glass transition point and / or a melting point. Specific examples of heat-meltable polymers include polyimide (PI), polyamideimide (PAI), polyamide, polyester, polyethylene terephthalate, polyphenylene sulfide, polysulfone, polyetherimide, polyethersulfone (PES), polyetheretherketone, and polyetherketoneketone. Among these heat-meltable polymers, polyetherimide (PEI), polyphenylsulfone (PPS), polyetheretherketone (PEEK), and polyetherketoneketone (PEKK), which have heat resistance and high mechanical strength, are preferred. Since the heat-meltable polymer is used by welding with a filler, the heat-meltable polymer used in the present invention does not include fluororesins, which generally have excellent non-adhesive properties. The shape of the heat-meltable polymer is not particularly limited, and examples thereof include powder, granules, granulated granules, and pellets. The average particle size of the heat-fusible polymer is preferably 0.1 to 300 μm, more preferably 1 to 100 μm, and further preferably 5 to 70 μm.
[0015] The heat-meltable polymer may be a commercially available product, such as ULTEM (registered trademark) series manufactured by SABIC and PPS manufactured by DIC Corporation.
[0016] B.Filling material The filler of the present invention may be inorganic particles, and may be selected according to the application of the coating film, taking into consideration its water resistance, chemical resistance, etc. The filler of the present invention is preferably made of a material that does not dissolve in water. Specific examples of the filler include metal powder, metal oxide (aluminum oxide, zinc oxide, tin oxide, titanium oxide, etc.), glass beads, glass flakes, glass particles, ceramics, silicon carbide, silicon oxide, calcium fluoride, carbon black, graphite, mica, barium sulfate, etc. The filler of the present invention is preferably heat-resistant to at least 200°C or more, preferably 300°C or more, and does not promote the decomposition of the fluororesin. Among the above fillers, silicon oxide, aluminum oxide, zinc oxide, tin oxide, and barium sulfate are preferred. The particle size of the filler is not particularly limited, but is preferably smaller than the average particle size of the heat-fusible polymer in terms of ease of uniform mixing with the heat-fusible polymer. The average particle size of the filler is from 0.1 to 30 μm, more preferably from 0.2 to 20 μm, and further preferably from 0.3 to 10 μm.
[0017] (Powder particles of the present invention) The powder particles of the present invention are powder particles in which (A) a heat-fusible polymer and (B) a filler are fused together. The powder particles can be obtained by premixing the heat-fusible polymer and the filler in water to form an aqueous dispersion, and then heating the mixture. The particle size of the filler is preferably small, but when a pulverization step described below is included, the filler is also pulverized in this step, so the particle size of the filler used is not particularly limited. The amount of the filler added is preferably 30 to 300 parts by weight, more preferably 50 to 200 parts by weight, and even more preferably 80 to 150 parts by weight, relative to 100 parts by weight of the polymer.
[0018] The particle size of the powder particles of the present invention is preferably 1 to 200 μm, and more preferably 150 μm or less. For example, if a sieve with a mesh size of 150 μm is used and the particles passing through the sieve are collected, particles having a particle size of 150 μm or less, usually particles having a particle size of about 5 to 150 μm, can be obtained. By using a sieve, particles having a uniform particle size can be easily obtained.
[0019] Generally, fluororesins have non-adhesive properties and are difficult to adhere to fillers. Therefore, if the contact interface between the fluororesin and the filler increases, the filler portion and the fluororesin laminate tend to peel off, and this causes the corrosion resistance, steam resistance, and durability of the portion to be deteriorated. In contrast, the powder particles of the present invention can reduce the contact interface between the filler and the fluororesin added later by fusing and integrating the heat-fusible polymer and the filler as described above. As a result, it is possible to obtain a coating film that has excellent adhesion between the substrate and the fluororesin layer, suppresses the intrusion of heat, moisture, corrosive substances, etc., prevents the fluororesin laminate from peeling off, and has improved corrosion resistance, steam resistance, and durability.
[0020] 2. Powder coating composition The powder coating composition of the present invention is a composition containing (A) powder particles having a heat-fusible polymer and (B) a filler fused thereto, and (C) a fluororesin powder.
[0021] C. Fluorine resin Examples of the fluororesin that can be used in the present invention include, but are not limited to, polytetrafluoroethylene (PTFE), tetrafluoroethylene-perfluoro(alkyl vinyl ether) copolymer (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-hexafluoropropylene-perfluoro(alkyl vinyl ether) copolymer, tetrafluoroethylene-ethylene copolymer, polyvinylidene fluoride, polychlorotrifluoroethylene, and chlorotrifluoroethylene-ethylene copolymer.
[0022] The fluororesin of the present invention is preferably a hot melt type fluororesin that exhibits melt fluidity at or above its melting point. Among them, from the viewpoint of the non-adhesiveness and heat resistance of the coating film, hot melt type perfluororesins such as low molecular weight PTFE, PFA, FEP, and tetrafluoroethylene-hexafluoropropylene-perfluoro(alkyl vinyl ether) copolymers can be preferably used, and PFA can be particularly preferably used.
[0023] The alkyl group of the perfluoro(alkyl vinyl ether) in the PFA preferably has 1 to 5 carbon atoms, and among these, perfluoro(propyl vinyl ether) (PPVE), perfluoro(ethyl vinyl ether) (PEVE), and perfluoro(methyl vinyl ether) (PMVE) are particularly suitable. The amount of the perfluoro(alkyl vinyl ether) in the PFA is preferably in the range of 1 to 50% by weight.
[0024] The fluororesin used in the present invention is preferably one that is melt moldable and has a melt flow rate (MFR) of (1-100) g / 10 min, preferably (1-70) g / 10 min at 372° C.±1° C. Here, several copolymers with different MFRs may be mixed and used to have a melt flow rate (MFR) of (1-100) g / 10 min, preferably (1-70) g / 10 min at 372° C.±1° C.
[0025] The fluororesin of the present invention may be, for example, fluororesin particles having a so-called core-shell structure made of fluororesins with different melting points, as described in Patent Document 3. The fluororesin having a multilayer structure made of at least two kinds of fluororesins with different melting points preferably has an outermost layer of 90 to 5% by weight of fluororesin and an inner layer of 10 to 95% by weight of high-melting-point fluororesin. The ratio of the outermost layer to the inner layer can be selected in consideration of the desired chemical resistance and gas permeability, linear expansion coefficient, maximum strength, etc. Such a fluororesin can be obtained as PFA particles containing PTFE, for example, by dispersing PTFE particles in a polymerization medium in a PFA polymerization tank in advance to initiate polymerization of PFA.
[0026] The fluororesin powder of the present invention may be any powder of the fluororesin, and has an average particle size of 0.05 to 75 μm, preferably 5 to 40 μm, and more preferably 5 to 30 μm. The fluororesin powder of the present invention can be obtained by powdering the fluororesin by a conventionally known method, but a commercially available product may also be used. Examples of commercially available products include Teflon (registered trademark) MJ-102, MJ-103, etc., manufactured by Mitsui-Chemours Fluoroproducts Co., Ltd., and Teflon (registered trademark) 532G-5011, etc., manufactured by Chemours.
[0027] (Powder coating composition of the present invention) The powder coating composition of the present invention is a composition containing the powder particles of the present invention and a fluororesin powder, that is, a composition containing powder particles to which (A) a heat-fusible polymer and (B) a filler are fused, and (C) a fluororesin powder. The powder coating composition of the present invention contains 80-50% by weight of powder particles and 20-50% by weight of fluororesin powder, preferably 75-55% by weight of powder particles and 25-45% by weight of fluororesin powder, and more preferably 60-70% by weight of powder particles and 40-30% by weight of fluororesin powder, based on the total amount of the powder coating composition. If the content of the fluororesin powder is too high, the adhesion to the substrate may decrease, and if it is too low, the adhesion to layers containing other fluororesins may decrease.
[0028] (optional ingredient) In the powder coating composition of the present invention, in addition to the powder particles and the fluororesin powder, any additive may be further contained as necessary. The additive is not particularly limited, and may be, for example, one used in a general coating composition. The additive may be, for example, a pigment, a filler, a leveling agent, a solid lubricant, a moisture absorbent, a surface conditioner, an ultraviolet absorber, a light stabilizer, a plasticizer, a color separation inhibitor, a scratch inhibitor, an antifungal agent, an antibacterial agent, an antioxidant, an antistatic agent, a silane coupling agent, etc.
[0029] Specific examples of the additives include color pigments such as carbon, titanium oxide, red iron oxide, and mica, anti-rust pigments, calcined pigments, extender pigments, lustrous flat pigments, scaly pigments, wood flour, quartz sand, carbon black, clay, talc, diamond, fluorinated diamond, corundum, silica stone, boron nitride, boron carbide, silicon carbide, fused alumina, tourmaline, jade, germanium, zirconium oxide, zirconium carbide, chrysoberyl, topaz, beryl, garnet, glass, glass powder, mica powder, metal powder (gold, silver, copper, platinum, stainless steel, aluminum, etc.), various reinforcing materials, various extenders, conductive fillers, and the like.
[0030] The content of the additives is preferably 0 to 10.0% by weight, more preferably 0 to 5.0% by weight, based on the powder composition. The powder coating composition of the present invention is usually suitably used as a primer coating (undercoat) for adhering a fluororesin layer to a substrate, but can also be used as a one-coat coating without using a primer coating.
[0031] (Creation of coating film) The powder coating composition of the present invention can be applied to a substrate and heated to form a coating film. The substrate is not particularly limited, and examples thereof include metal substrates such as iron, aluminum, copper, and stainless steel, glass, ceramic, and heat-resistant plastic substrates. The method of application to the substrate is not particularly limited, and can be appropriately selected depending on the form of the substrate, and a conventionally known method such as electrostatic powder coating can be used. The thickness of the coating depends on the application, and is, for example, 20 to 150 μm, preferably 30 to 100 μm.
[0032] The coating film containing the powder coating composition of the present invention has non-adhesive properties, and at the same time, has excellent corrosion resistance, steam resistance, and adhesion to substrates. Therefore, it can be widely used in office automation, chemical corrosion protection, food heat processing equipment, sliding materials, automobiles, building materials, and semiconductor manufacturing equipment components.
[0033] 3. Method for producing powder particles and powder coating composition (Method of manufacturing powder particles) The powder particles of the present invention can be obtained by the following steps (1) to (3). (1) a step of mixing a heat-fusible polymer and a filler in water to obtain an aqueous dispersion; (2) heating the aqueous dispersion to remove water and obtain a solid; and (3) A step of pulverizing the solid to obtain powder particles.
[0034] In step (1), the heat-meltable polymer and the filler are added to water and dispersed. The water used here is preferably water that is usually called pure water, from which impurities such as ions have been removed by distillation or ion exchange. As a method for dispersing the heat-meltable polymer and the filler, in addition to dispersion treatment using a normal stirrer, a homogenizer, an ultrasonic disperser, a colloid mill, a bead mill, etc. can be used. Here, a dispersant such as a surfactant may be added, but it is preferable not to add a dispersant because this can reduce the burden on the environment.
[0035] In step (2), the dispersion obtained in step (1) is heated and dried to remove moisture. The drying temperature can be, for example, 60 to 160°C, preferably 80 to 140°C, and more preferably 100°C to 120°C. The drying time can be 5 minutes to 10 hours, preferably 1 hour to 8 hours, more preferably 2 hours to 6 hours, and even more preferably 3 hours to 5 hours. The drying apparatus can be a method of drying in an oven set at a predetermined temperature, or a method using, for example, an arch dryer, a floating dryer, a drum dryer, an infrared dryer, or the like. Since no organic solvent is used in the production method of the present invention, the drying process can be carried out without requiring special equipment such as explosion-proof equipment.
[0036] It is preferable to include a step of heating at a temperature equal to or higher than the glass transition point of the heat-fusible polymer following step (2). By including this step, powder particles in which the heat-fusible polymer and the filler are fused together can be obtained. By forming powder particles in which the heat-fusible polymer and the filler are fused together, the filler is less likely to be detached from the powder particles, and as a result, a coating film with better corrosion resistance and steam resistance can be obtained.
[0037] Step (3) is a step of pulverizing the solid obtained in step (2). For example, a pulverizer such as a high-pressure homogenizer, grinder, impact pulverizer, bead mill, jet mill, hammer mill, pin mill, ball mill, tube mill, pulverizer, air sweep mill, disk mill, vibration mill, stone mill, planetary motion mill, etc. can be used as a pulverizing method. After pulverization, it is preferable to adjust the particle size using a sieve. The opening of the sieve used can be appropriately selected depending on the size of the particles obtained in step (3), but it is preferable to set it to 150 μm or less from the viewpoint of uniformity of the powder coating composition.
[0038] (Method of producing powder coating composition) The powder coating composition of the present invention can be produced by adding a fluororesin powder and mixing it in step (4) in addition to steps (1) to (3) in the above-mentioned method for producing powder particles. In the mixing, a conventionally known method for mixing powders can be used. For example, any method can be used, such as a method of putting the powders to be mixed in one container and rotating the container itself, a method of mixing the powders to be mixed in a container with a mixing blade, or a method of stirring and mixing with an air flow. EXAMPLES
[0039] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0040] <Raw materials> A. Heat-melting polymer 1. Polyetherimide (PEI) ULTEM 1010P Powder (SABIC INNOVATIVE PLASTICS, glass transition point 217℃) 2. Polyphenylene sulfide (PPS) Manufactured by DIC Corporation. Average particle size: 12-16μm, melting point: 278℃ 3. Polyetheretherketone (PEEK) VICOTE® 704 (manufactured by VICTREX, melting point 343°C) 4. Polyetherketoneketone (PEKK) KSTONE® CC-5601 (manufactured by Shandong Kaisheng New Materials Co., Ltd., melting point 308°C) B.Filling material 1. Barium sulfate (BaSO4) BLANC FIXE MICRO (manufactured by SACHTLEBEN, average particle size 0.8μm) 2. Aluminum oxide (Al2O3) SGA-16 (manufactured by ALMATIS, average particle size 0.4μm) 3. Carbon Black (CB) MPC Channel Black (Keystone Aniline) C. Fluorine resin PFA (MJ-102, Mitsui-Chemours Fluoroproducts, average particle size 20 μm)
[0041] [Example 1] (Preparation of Powder Coating Composition) (Step (1)) 3.2 L of pure water was placed in a 5 L beaker, and 1 kg of barium sulfate and 1 kg of PEI were added thereto, followed by stirring at 300 rpm for 30 minutes using a stirrer (manufactured by YAMATO SCIENTIFIC CO. LTD.). (Step (2)) The dispersion obtained in step (1) was left to stand for 2 hours in an oven set at 120° C. to remove moisture, and then left to stand for another 2 hours in an oven set at 300° C. (Step (3)) The solid obtained in step (2) was pulverized in a mill grinder (manufactured by Osaka Chemical Co., Ltd.) at 25,000 rpm, and then passed through a sieve with 150 μm openings to obtain powder particles. (Step (4)) 350 g of PFA was added to 650 g of the powder particles obtained in step (3) to obtain a powder coating composition. The blend ratio of PEI:BaSO4:PFA was 32.5%:32.5%:35.0%.
[0042] (Preparation of test specimens) A 50mm x 100mm aluminum (A1050) was used as a substrate, and about 10mm on one side was masked and shot blasted with #60 alumina. The powder coating composition was then electrostatically powder coated using a powder coating spray gun (PARKER IONICS GX355HW) to form a primer layer with a thickness of 50μm. The masking tape was peeled off, and PFA (MJ-102) was electrostatically powder coated on the primer layer using a powder coating spray gun, and baked at 390°C (substrate temperature) for 30 minutes to form a topcoat layer, and the resulting fluororesin laminate was used as a test piece.
[0043] (Adhesion measurement) Using the above test piece, the fluororesin laminate was cut to a width of 10 mm in the short side direction, and the masking portion (the fluororesin laminate portion without the primer layer) was peeled off toward the fluororesin laminate portion with the primer layer. The peeled off masking portion (the fluororesin laminate portion without the primer layer) was protected with masking tape. Using a Tensilon universal testing machine (manufactured by A&D Co., Ltd.), the portion protected with the masking tape was clamped in the chuck of the testing machine and pulled at a speed of 50 mm / min in accordance with the measurement method for the peel strength of adhesives (90 degree peel test method) specified in JIS K 6854, and the adhesion force of the fluororesin laminate portion with the primer layer was measured. The unit is gf / cm. The adhesion force was measured for each of the test pieces before and after the steam resistance test described below.
[0044] (Steam resistance test) Using a pressure cooker tester (PCT VS-277, manufactured by Kyosin Engineering Corporation), the above test pieces were left in steam at 170°C and 0.8 MPa for 300 hours, and then left to cool to room temperature. The presence or absence of blisters (eczema-like swelling) was observed visually and under a microscope. Those without blisters were evaluated as ◯, and those with blisters were evaluated as ×. The above adhesion force was measured using the test pieces after the steam resistance test.
[0045] [Examples 2 to 4] Test pieces were obtained in the same manner as in Example 1, except that the amounts of PEI and barium sulfate added were changed to the blend ratios shown in Table 1, instead of 32.5% in Example 1, and 32.5% in Example 1.
[0046] [Example 5] A test piece was obtained in the same manner as in Example 1, except that PEEK was used instead of PEI in Example 1, and step 2 was carried out at the following temperature. (Step (2) (Example 5)) The dispersion obtained in step (1) was left to stand for 2 hours in an oven set at 120° C. to remove moisture, and then left to stand for another 2 hours in an oven set at 350° C.
[0047] [Example 6] Test pieces were obtained in the same manner as in Example 1, except that PEKK was used instead of PEI in Example 1, and step 2 was carried out at the following temperature. (Step (2) (Example 6)) The dispersion obtained in step (1) was left to stand for 2 hours in an oven set at 120° C. to remove moisture, and then left to stand for another 2 hours in an oven set at 310° C.
[0048] [Example 7] A test piece was obtained in the same manner as in Example 1, except that the step (2) in Example 1 was changed to the following step (2'). (Process (2')) The dispersion obtained in step (1) was left to stand in an oven set at 120° C. for 2 hours to remove moisture.
[0049] [Example 8] A test piece was obtained in the same manner as in Example 5, except that the step (2) in Example 5 was changed to the following step (2'). (Process (2')) The dispersion obtained in step (1) was left to stand in an oven set at 120° C. for 2 hours to remove moisture.
[0050] [Comparative Example 1] A composition was obtained by mixing 325g of PEI, 325g of barium sulfate, and 350g of PFA in a weight ratio. The blending ratio of PEI:BaSO4:PFA was 32.5%:32.5%:35.0%. Using the obtained composition, a test piece was obtained in the same manner as in Example 1 (preparation of test piece).
[0051] [Comparative Examples 2 to 6] Test pieces were obtained in the same manner as in Comparative Example 1, except that the amounts of PEI and barium sulfate added were changed to the blending ratios shown in Table 1, instead of 32.5% PEI and 32.5% barium sulfate used in Comparative Example 1.
[0052] The compounding ratios and test results of the Examples and Comparative Examples are shown in Table 1. Example 1 and Comparative Example 1 have the same composition, but Example 1 uses a powder coating composition produced by the manufacturing method of the present invention, while Comparative Example 1 is an example using a composition obtained by simply mixing materials. It can be seen that Example 1 has clearly greater adhesion. Similar results were obtained in Comparative Examples 2 to 6, which correspond to Examples 2 to 4 and 6 to 8.
[0053] [Table 1]
[0054] The present invention is not limited to the disclosed contents of the examples described in this specification or the embodiments of the invention disclosed in this specification, but includes the contents of the invention that have been appropriately modified based on the matters disclosed in this specification, etc., as long as they are not contrary to the spirit of the present invention. [Industrial Applicability]
[0055] The powder coating composition of the present invention has excellent adhesion between the substrate and the fluororesin layer, and prevents the intrusion of heat, moisture, corrosive substances, etc., thereby preventing peeling of the fluororesin laminate, and can provide a coating film with improved corrosion resistance, steam resistance, and durability.
Claims
1. Powder particles obtained by premixing a heat-fusible polymer and a filler in water to form an aqueous dispersion, and then heating the mixture.
2. 2. The powder particles according to claim 1, wherein the heat-fusible polymer and the filler are fused together.
3. 2. The powder particles according to claim 1, wherein the heat-fusible polymer is at least one selected from the group consisting of polyimide, polyamideimide, polyamide, polyester, polyethylene terephthalate, polyphenylene sulfide, polysulfone, polyetherimide, polyethersulfone, polyetheretherketone, and polyetherketoneketone.
4. 2. The powder particles according to claim 1, wherein the heat-fusible polymer is at least one selected from the group consisting of polyphenylene sulfide, polyetherimide, polyetheretherketone, and polyetherketoneketone.
5. 2. The powder particles according to claim 1, wherein the filler is at least one inorganic particle selected from the group consisting of silicon carbide, silicon oxide, aluminum oxide, zinc oxide, tin oxide, titanium oxide, barium sulfate, and carbon black.
6. The powder particles according to claim 1, comprising 30 to 300 parts by weight of a filler based on 100 parts by weight of the heat-fusible polymer.
7. 2. The powder particles according to claim 1, having a particle size of 150 μm or less.
8. A powder coating composition comprising the powder particles according to any one of claims 1 to 7 and a fluororesin powder.
9. 9. The powder coating composition according to claim 8, wherein the fluororesin powder comprises a melt processable fluororesin.
10. 9. The powder coating composition according to claim 8, wherein the fluororesin powder is a perfluororesin.
11. 9. The powder coating composition according to claim 8, comprising 80 to 50% by weight of the powder particles and 20 to 50% by weight of the fluororesin powder, based on the total weight of the powder coating composition.
12. (1) mixing a heat-fusible polymer and a filler in water to obtain an aqueous dispersion; (2) heating the aqueous dispersion to remove water to obtain a solid; (3) pulverizing the solid to obtain powder particles; A method for producing powder particles comprising the steps of:
13. The method for producing powder particles according to claim 12, further comprising a step of heating at a temperature equal to or higher than the glass transition point of the heat-fusible polymer subsequent to the step (2).
14. (1) mixing a heat-fusible polymer and a filler in water to obtain an aqueous dispersion; (2) heating the aqueous dispersion to remove water to obtain a solid; (3) pulverizing the solid to obtain powder particles; (4) adding and mixing a fluororesin powder with the powder particles to obtain a powder coating composition; A method for producing a powder coating composition comprising the steps of:
Citation Information
Patent Citations
Fluororesin molding method and fluororesin molding
JP2007320267A
Polymer particle, aqueous dispersion containing the same, and fluororesin coating material composition using the same
JP2013231098A
Powdery primer composition
JP2022137848A